Marketing Innovations through Information Technology Techniques - A Study on Pharmaceutical Products - Veeraiah, P.; Shivanaga Sreenu, I. (Indian Journal of Marketing, 2006)
An innovation is developing a new idea and putting it into practice. In the competitive strategy of a private enterprise in a market-driven business environment, the term ’innovation’ is used to refer to the process of bringing valuable new products (goods and services) to the market i.e., from the idea/concept formulation stage to the successful launching of a new or improved product in the marketplace. Through innovation an enterprise seeks to deliver unique new value to its customers. In this context, ’marketing’ is the understanding of that unique new value and communicating it to the current and potential customers of a business so that the product sells itself.